Julius Caesar : modern English version side-by-side with full original text - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Shakespeare made easy., 1985)
Presents the original text of Shakespeare's play side by side with a modern version, discusses the author and the theater of his time, and provides quizzes and other study activities.